Analisis Pemetaan Mutu Pendidikan SMP N 1 Boja Kabupaten Kendal - Ngatini; Titik Haryati (Melati Institute, 2024)
This study aims to describe the analysis of education quality mapping at SMP N 1 Boja, Kendal Regency. The research approach used is qualitative. This type of research is a case study. This research uses triangulation of sources and methods. Data analysis with three steps: data reduction, presenting data, and drawing conclusions. The results showed that: Implementation at SMP N 1 Boja Kendal Regency has generally gone well. The independent curriculum is well implemented with good learning and assessment processes. Changes in several components of the curriculum structure of SMP N 1 Boja Kendal Regency appear to provide challenges for teachers in preparing learning tools in accordance with applicable regulations. In the end, the achievement of learning quality is included in the medium category, not as expected. Therefore, further studies and action plans are needed to improve the quality of learning.